PERILAKU PEMELIHARAAN KESEHATAN GIGI DAN MULUT TERHADAP STATUS KEBERSIHAN GIGI DAN MULUT (OHI-S) WARGA SAMIN SUROSENTIKO KABUPATEN BLORA - Betty Saptiwi; Muchtar Hanafi; Dian Purwitasari (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2019)
Behavior has an important role to influence oral hygiene status. An important component in behavior is knowledge, attitudes and actions. The residents of Samin Surosentiko Blora Regency have a characteristic ignoring the appearance and cleanliness of themselves and the surrounding environment. The results of the OHI-S examination of 50 people from Samin Surosentiko in Blimbing Hamlet, Sambongrejo Village, Sambong District, Blora Regency, found to have 30 people (60%) who had OHI-S status with poor criteria accompanied by tooth and mouth problems. The purpose of this study was to determine the effect of behavior (knowledge, attitudes, and actions) on the maintenance of teeth and mouth on oral hygiene status (OHI-S) of Samin Surosentiko Residents in Blora Regency. Type of research used was descriptive analytic. Research design was survey with a cross sectional approach. The population in this study were residents of Samin Surosentiko in Blimbing Hamlet, Sambongrejo Village, Sambong Subdistrict, Blora Regency aged 20-36 years and had a set of 180 teeth. Samples were taken by random sampling of 20% of the population of 36 people. Descriptive data analysed by cross tab and statistically using Chi Square Test. Results showed that the majority of respondents had oral health maintenance behaviors in poor criteria with a bad OHI-S status (41.7%). The Chi Square Test results showed that there was an effect on oral health maintenance behavior on OHI-S status (p = 0.000). Conclusion of the study was that there was an effect of oral health maintenance behavior on OHI-S status in Samin Surosentiko residents in Blora Regency (p = 0.000), where the attitude component is the most influential (p = 0.000).